Before You Spray - Matt Smith (EDIS)
We often spend the most time thinking about pesticide safety and best management practices when we are actually spraying in the field. Intuitively, this makes sense. You’re outside, you’re spending the most time potentially exposed to the pesticide, and a gust of wind in the wrong direction could send it flying back into your face. However, your first interaction with pesticides each spray day takes place well before you step foot in the field. There are several things you can do before spraying begins to help ensure a safe and efficient spray day, and this article will cover a few of them, including identifying the target pest, ensuring your pesticide label is up-to-date, calibrating equipment, wearing the proper PPE during mixing and loading, and testing product compatibility.